Comprehensive Time-Course Transcriptome and Co-expression Network Analyses Identify Salt Stress Responding Mechanisms in Chlamydomonas reinhardtii Strain GY-D55 - Zhang, Luo-Yan; Xing, Zhao-Tian; Chen, Li-Qian; Zhang, Xue-Jie; Fan, Shou-Jin (Frontiers in Plant Science, 2022)
It is highly necessary to understand the molecular mechanism underlying the salt stress response in green algae, which may contribute to finding the evolutionary cues of abiotic stress response in plants. Here we reported a comprehensive temporal investigation of transcriptomes using data at eight different time points, from early stage (2 h) to late stage (up to 96 h) in Chlamydomonas reinhardtii GY-D55 cells. The principal component analysis (PCA) of transcriptome profiles showed that the samples of early and late stage were well separated. A total of 12,445 genes were detected as differentially expressed genes. There were 1,861/2,270 common up-/down-regulated genes for each time point compared with control samples. Samples treated with salt for 2, 8, and 24 h had a relatively large number of characteristic up-/down-regulated genes. The functional enrichment analysis highlighted the timing of candidate regulatory mechanisms for salt stress responses in GY-D55 cells. Short time exposure to salt stress impaired oxidation reduction, protein synthesis and modification, and photosynthesis. The algal cells promoted transcriptional regulation and protein folding to deal with protein synthesis/modification impairments and rapidly accumulated glycerol in the early stage (2-4 h) to cope with osmotic stress. At 12 and 24 h, GY-D55 cells showed increased expressions of signaling and photosynthetic genes to deal with the damage of photosynthesis. The co-expression module blue was predicted to regulate endoplasmic reticulum (ER) stress at early time points. In addition, we identified a total of 113 transcription factors (TFs) and predicted the potential roles of Alfin, C2C2, and MYB family TFs in algal salt stress response.